Heart Slices to Model Cardiac Physiology - Meki, Moustafa H.; Miller, Jessica M.; Mohamed, Tamer M. A. (Frontiers in Pharmacology, 2021)
Translational research in the cardiovascular field is hampered by the unavailability of cardiac models that can recapitulate organ-level physiology of the myocardium. Outside the body, cardiac tissue undergoes rapid dedifferentiation and maladaptation in culture. There is an ever-growing demand for preclinical platforms that allow for accurate, standardized, long-term, and rapid drug testing. Heart slices is an emerging technology that solves many of the problems with conventional myocardial culture systems. Heart slices are thin (<400 µm) slices of heart tissue from the adult ventricle. Several recent studies using heart slices have shown their ability to maintain the adult phenotype for prolonged periods in a multi cell-type environment. Here, we review the current status of cardiac culture systems and highlight the unique advantages offered by heart slices in the light of recent efforts in developing physiologically relevant heart slice culture systems.